2017
DOI: 10.1242/dev.152587
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factors: key players in regeneration and tissue repair

Abstract: Tissue injury initiates a complex repair process, which in some organisms can lead to the complete regeneration of a tissue. In mammals, however, the repair of most organs is imperfect and results in scar formation. Both regeneration and repair are orchestrated by a highly coordinated interplay of different growth factors and cytokines. Among the key players are the fibroblast growth factors (FGFs), which control the migration, proliferation, differentiation and survival of different cell types. In addition, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 125 publications
(184 reference statements)
2
155
0
2
Order By: Relevance
“…An important step in the development of endochondral bone is reactivation based on the time of the bony injury, as most of FGFs and FGFRs seem upregulated during this step. Therefore, this confirms their roles in bone healing (Maddaluno, Urwyler, & Werner, 2017). A recent study has shown that the healing of calvarium defects is directly linked with FGFs.…”
Section: Fibroblast Growth Factorssupporting
confidence: 81%
“…An important step in the development of endochondral bone is reactivation based on the time of the bony injury, as most of FGFs and FGFRs seem upregulated during this step. Therefore, this confirms their roles in bone healing (Maddaluno, Urwyler, & Werner, 2017). A recent study has shown that the healing of calvarium defects is directly linked with FGFs.…”
Section: Fibroblast Growth Factorssupporting
confidence: 81%
“…FGF15/19 is secreted from the enterocytes under physiological conditions, circulates to the liver, and activates Fgfr4 in the presence of β‐Klotho. Activation of Fgfr4 leads to activation of several signaling pathways, including MAPK and Stat3, which are believed to be the major mechanism to suppress BA synthesis and promote cell cycle progression . Activation of these pathways could contribute to the priming of liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Fgfr4 leads to activation of several signaling pathways, including MAPK and Stat3, which are believed to be the major mechanism to suppress BA synthesis and promote cell cycle progression. (13,22,34) Activation of these pathways could contribute to the priming of liver regeneration. The early stage of liver regeneration (approximately 0 hours to 4 hours after PHx in mice) is known as the "priming" phase, which requires an orchestration of various molecular signaling pathways and complex tissue interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors in the inflammatory phase initiate angiogenesis and granulation by excreting growth factors such as TGF-β, IGF-1, MIP-1, MCP-2, TNF-α that trigger cell movement into the wound and play an important role in extracellular matrix formation. Growth factors VEGF and iNOS promote angiogenic activity [32]. The inflammatory phase follows the phase of proliferation characterized by tissue granulation and angiogenesis.…”
Section: Role Of Dpp Iv/cd26 In Wound Healing In Diabetesmentioning
confidence: 99%